A patient choice‐driven lifestyle intervention lowers HbA1c in type 2 diabetes: A feasibility study - Nathan R. Weeldreyer; Mindy L. McEntee; Matthew P. Martin; Chong D. Lee; Farshad Fani Marvasti; Glenn A. Gaesser; Rodger Kessler; Siddhartha S. Angadi (Physiological Reports)
Abstract Type 2 diabetes (T2D) is a common metabolic disorder in which only 25% of patients meet management targets. While the primary care setting is positioned to provide lifestyle management education, studies are lacking which integrate behavior interventions in this setting utilizing clinic staff. Thus, we evaluated a 90‐day lifestyle intervention for management of glycemia at a family practice clinic administered by clinic medical assistants. Twenty patients with non‐insulin‐dependent T2D completed a 90‐day intervention driven by patient choices of nutrition and physical activity. Medical assistants were trained by members of the study team and administered the intervention under nurse practitioner supervision. HbA1c trended toward significant reduction 8.59 ± 0.9% to 8.15 ± 1.2% (p = 0.051, 95% CI: −0.88 to 0.003). Modest reductions were observed for waist circumference (115.5 ± 12.6 vs. 112.5 ± 15.2 cm; p = 0.014, 95% CI: −5.66 to −0.26), body weight (97.7 ± 21.9 vs. 95.6 ± 23.9 kg; p = 0.016. 95% CI: −3.84 to −0.31), and BMI (33.7 ± 7.2 vs. 32.8 ± 7.5 kg/m2; p = 0.028, 95% CI: −1.29 to −0.12). This 90‐day, patient choice‐intervention was successful at lowering HbA1c in patients with T2D. Our study is limited by a lack of control group, and results should be interpreted as such. These data have implications for team‐based care models in clinic settings to improve health outcomes in patients with T2D.